Percutaneous Secundum Atrial Septal Defect Closure: Failure Rate and Procedural Predictors - Yuwono, Elien; Gunawijaya, Eka; Yantie, Ni Putu Veny Kartika (Cell and BioPharmaceutical Institute, 2024)
Background: Percutaneous atrial septal defect (ASD) closure is one of therapeutic options for patients with a suitable ASD anatomy, however in developing countries, the exact figure and procedural characteristics remain unknown. Therefore, this study was conducted to identify the failure rate and procedural predictors of the percutaneous ASD closure.Materials and methods: A retrospective study using a database of all patients undergoing percutaneous ASD closure was conducted between March 2010 to November 2023. Patients who developed a pulmonary hypertensive crisis during the procedure were excluded. Procedural and echocardiographic parameter were measured and analyzed.Results: A total of 112 samples were included in this study, 74.1% were female and 55.36% were pediatric patients. The failure rate was 12.5% (n=14) with diameter index was higher in the failed group. Unpaired T-test revealed that ASD size was one of the predictor failure in pediatric patients (mean diameter: 24.7±6.46 mm vs. 16.36±5.94 mm, p=0.001). There were no statistically significant variations in rim diameters, while compared with all patients with appropriate rims (rim ≥7mm), the failure rate was higher in patients with two rims measuring between 5.9 and 6.9 mm and rims less than 5 mm. Two patients presented with device embolization and required surgical device removal.Conclusion: The failure rate of percutaneous ASD closure was 12.5%. A larger ASD increases the risk of failure of percutaneous closure in pediatric patients. Furthermore, patient with 5-6.9 mm on two or more rims as well as those with rim less than 5 mm, have a higher failure rate.Keywords: secundum atrial septal defect, percutaneous closure, failure rate